2006
DOI: 10.1055/s-2006-926281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Halogenated 1,2,4-Triazole Nucleoside Analogues with High Potential for Chemical Modifications

Abstract: 1,2,4-Triazole nucleoside analogues bonded at N-1 of the base were synthesized by addition of N-halo-3,5-dibromo-1,2,4-triazoles to 1,2-unsaturated carbohydrate derivatives (glycals). Examples are given for 1,5-anhydro-3,4,6-tri-O-acetyl-2-deoxy-D-arabino-hex-1-enitol (tri-O-acetyl-D-glucal), and 1,5-anhydro-3,4,6-tri-O-benzyl-2-deoxy-D-arabino-hex-1-enitol (tri-O-benzyl-D-glucal), respectively. The graduated reactivity of the three halogens [C-5 (triazole) > C-2 (sugar) > C-3 (triazole)] in the addition produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…By using 7 , only two different regioisomers can be formed ( N 1 / N 2 vs N 4 ) in the alkylation step. Literature reference suggested that the following debromination could be performed selectively on the bromo substituent vicinal to the alkylated nitrogen, leaving the other bromide substituent behind as a functional handle for the methylation …”
Section: Process Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…By using 7 , only two different regioisomers can be formed ( N 1 / N 2 vs N 4 ) in the alkylation step. Literature reference suggested that the following debromination could be performed selectively on the bromo substituent vicinal to the alkylated nitrogen, leaving the other bromide substituent behind as a functional handle for the methylation …”
Section: Process Developmentmentioning
confidence: 99%
“…3,5-Dibromo-1H-1,2,4-triazole (7) caught our attention as a starting material for the desymmetrization approach as it is inexpensive and readily available on large scale. 4 By using 7, only two different regioisomers can be formed (N 1 /N 2 vs N 4 ) in the alkylation step. Literature reference suggested that the following debromination could be performed selectively on the bromo substituent vicinal to the alkylated nitrogen, leaving the other bromide substituent behind as a functional handle for the methylation.…”
Section: ■ Process Developmentmentioning
confidence: 99%
See 2 more Smart Citations